GENETIC VARIABILITY OF Maytenus ilicifolia NATURAL POPULATIONS THROUGH RAPD MARKER - BITTENCOURT, Juliana Vitoria Messias (Scientia Agraria, 2001)
Maytenus ilicifolia is a shrub with natural occurrence from Ombrophilous Mixed Forest (Araucaria Forest). This species is used by Brazilian indigenous and local people for stomachs illness. The fragmentation of the Araucaria Forest together with the therapeutic comprovation and use in large scale of Maytenus ilicifolia had caused big devastation of natural populations. This resulted in lost of genetic complex of this medicinal resources. It is urgent to elaborate strategies of genetic conservation and domestication of this germplasm. The goal of this study was to determine the genetic variability in natural populations of Maytenus ilicifolia through DNA polymorphism using RAPD markers. Three populations were studied, one in Lapa city and two in Guarapuava region. These areas have different geology and landscape characteristics. Seven RAPD primers were selected, which produced 52 markers in Maytenus ilicifolia, 44 of them were polymorphic. The genetic distance analysis was made by pair-group of the samples following the numerical taxonomy and using the similarity cofficient of Jaccard. With the genetic distance was made a dendrograme, which separated them in four main groups, two for the region of Lapa and two for Guarapuava. The groups were following flue geological characteristics and soil groups where the plants were growing. The genetic variability of Guarapuava populations, when compared with Lapa, show as a large similarity among their groups. Strategies for genetic conservation of Maytenus ilicifolia should be desing following the local ecogeographic parameters, collecting samples in each environmental compartment.